Intramolecular Asymmetric Cyclopropanation Using Air-Stable Alkylboronic Esters - Vedani, Luca; Gnägi-Lux, Manuel; Dénès, Fabrice; Renaud, Philippe (Synlett, 2023)
The preparation of polysubstituted bicyclo[3.1.0]hexanes starting from air-stable substituted pent-4-en-1-ylboronic acid esters has been investigated. The method involves a Matteson homologation with LiCHCl2, leading to 1-chlorohex-5-en-1-ylboronic acid ester intermediates. The subsequent intramolecular cyclopropanation step was performed in a one-pot process. With pinacol boronic esters, the cyclopropanation step was either performed thermally at 140 °C or at 70 °C after in situ transesterification to form a catechol boronic ester. This last approach is suitable for the preparation of enantioenriched bicyclo[3.1.0]hexanes using either chiral-auxiliary control or by taking advantage of the sparteine-controlled enantioselective boroalkylation of alcohols.
Keywords: cyclopropanation; boronic esters; Matteson homologation; chloroalkylboronates; bicyclo[3.1.0]hexanes; fused cyclopropanes